Advocating Mathematics Teacher Research Prowess for Improved Professionalism - Joshua Abah ABAH (SAINTIS Publishing, 2018)
While serving in the field of practice, teachers have continued to hold to the view that research is an activity carried out by professional researchers based outside the basic schools. This is because traditionally, class teachers have never been expected to comment on the theory and practice of their work. However, recent push by the Teacher Research movement across the globe has emphasized teacher research as a process in which educators note problems in the context of their own schools and classrooms and propose investigative methods appropriate to address the problems. On this premise, this review first considers the ramification of mathematics teacher research in improving professionalism in the teaching and learning of mathematics. Secondly, teacher professionalism in mathematics education was given a detailed coverage. Thirdly, the task of mathematics teachers as researchers was considered. The role of higher education in nurturing fruitful collaborations with basic schools was discussed along with the implications of mathematics teacher research for classroom practice in Nigeria.